Analisis Karakteristik DAS Tapakis Berbasis Sistem Informasi Geografis Untuk Analisis Hidrograf Satuan Sintetik - Zahri, Rifqi; Fauzi, Manyuk; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Information of characteristic watershed is very important to analysis tranformation rainfall be runoff. Study area in the river akuaman, that there is watershed of tapakis. One of the methods to analyzes the characteristic of a stream zone is by utilizing Digital Elevation Model (DEM). DEM`s data is processed by using the Geographical Information System Technology (GIS). The provided data and Geographical Information System is used to extract the characteristic of watersheds quickly, automatically, and integrated with other watershed`s data. By the availability of DEM`s data which is processed by using GIS application, is capable to produces the watershed characteristic`s data, which will be used to calculate the discharge of flood with Hidrograph Unit Syntetic method (HSS). The Hidrograph Unit Syntetic method which were used on this research are Gama I, Nakayasu, ITB-1, ITB-2, SCS, and Synder. The concept of syntetic unit of hydrograf with a value of control volume / run off must be approaching a value 1 mm of high direct run off (HDRo), so that known a method of syntetic unit of hydrograf can be applied to watershed. In a case study can be seen a all method of syntetic unit of hydrograf applicable to the watershed of Tapakis with the result is Gama I 0.77 mm , Nakayasu 1,01 mm , ITB I 1.00 mm , ITB II 1.00 mm , SCS 1.00 mm ,and Snyder 1,83 mm and the value of HDRo approaching 1 mm and the value of control volume below 5 %Key Word: Gama I, Nakayasu, SIG